Description of the mature larva and pupa of Anthonomus santacruzi Hustache (Coleoptera, Curculionidae), a biological control agent of Solanum mauritianum Scop. (Solanaceae), and remarks about its biology - Gosik, Rafał; Sasa, Archbold; Witkowski, Ed. T.f. (Zootaxa, 2017)
The mature larva and pupa of Anthonomus santacruzi Hustache (Coleoptera, Curculionidae) are illustrated and described for the first time. Biological data obtained from field-collected specimens are also presented and discussed. Lastly, an upgraded key for selected Anthonomini pupae is also given.